Modelling thermodynamic feedback on the metabolism of hydrogenotrophic methanogens. (21st September 2019) - Lynch, T.A.; Wang, Y.; van Brunt, B.; Pacheco, D.; Janssen, P.H.
Highlights: Model of anaerobic microbial growth incorporating thermodynamic constraints. Concentrations of substrates and products, and ATP yield impact thermodynamics . A threshold for substrate use emerges, which increases with greater ATP yield. Half saturation constant increases with increasing ATP yield per substrate. Changing the ATP yield results in differing ecological strategies. Abstract: The magnitude of the Gibbs free energy change of the substrate transformation that supports the growth of a microbe is decreased when the concentrations of the substrates are decreased and when the concentrations of the products of metabolism are increased. Microbes require a supply of ATP for cell maintenance and growth, and coupling the transformation of substrates to products with the formation of ATP also decreases the magnitude of the Gibbs free energy change. Here we include these three thermodynamic controllers (substrate and product concentration, and ATP formation) in a model of substrate transformation by hydrogenotrophic methanogens that results in a number of realistic behaviours. First, a threshold for substrate use emerges, below which the methanogen cannot metabolise its substrate. Under this model, microbes that capture more of the Gibbs free energy change from substrate transformation in the form of ATP have greater thresholds for their substrate, in line with observations of actual microbes. Second, an apparent saturation constant emerges that is controlled by the thermodynamics of the reaction. This increases with increasing ATP synthesis per substrate, so that methanogens that conserve more ATP grow faster at higher substrate concentrations, but are less competitive at low substrate concentrations. As a result, simply changing the ATP yield (moles of ATP per mole of substrate) results in methanogens with differing ecological strategies through thermodynamic impacts on their metabolism. Third, end-product inhibition through thermodynamic feedback can limit the growth of microbes, and those that capture more ATP per substrate are limited by smaller product concentrations than those that capture less ATP.